WHAT IS COST? - Cox, C. E. (The Accounting Review, 1930)
Abstract This article focuses on the movement towards refinement of terminology of accounting. The attempt of leaders in the field to give exact definition to the various accounting terms is evidenced chiefly by the activity of the Terminology Department of American Institute of Accountants. Not infrequently there is encountered in accounting literature the thought that accounting, being an aspect of applied economics, should be cognizant of the dictates of economic theory and should attempt to portray the concepts of the economist. It is the intention of the present article first to display the economic concept of cost of production and to follow that with the accounting concept so that when they stand in contrast any similarities or dissimilarities may become apparent. The concept of cost is truly fundamental in economic analysis. In fact one author has gone so far as to state that the backbone of economic science is the balancing of value against cost. It appears at the outset that before proceeding further in a consideration of the role which cost plays in the economic scheme of things it would be well to pause and examine the nature of cost as conceived by the economist.